The multi-sport program was influenced by the selection of athletes in football – a study of some coordination abilities, motor skills, and some anaerobic non-acidic abilities affecting high athletic performance. - hadj ahmed, Mourad (sports creativity, 2025)
The system for creating a champion athlete is comprehensive, requiring a suitable and well-rounded physique. No matter how skilled a coach is, they cannot create a champion from an unsuitable body. It is an indisputable fact that selecting the appropriate body type is the first step, followed by training and athletic practice. The importance of body type in achieving athletic excellence and creativity stems from its ability to predict the future physical characteristics of an individual, assuming their nutrition remains constant or changes within normal limits. Based on body type, children and adults are guided towards sports appropriate to them. Body type is one of the most stable, if not the most stable, selection criteria. The fundamental selection criteria include biological (physiological and morphological) factors. The physiological aspect encompasses the overall health of the body's systems, while the morphological aspect addresses physical characteristics such as total body height, limb lengths, trunk length, and weight, all of which have health implications. Furthermore, physical activity is of paramount importance. In this regard, we note that physical activity is a significant factor influencing growth, especially during childhood. The stages of childhood and adolescence are crucial, as the body's systems, especially muscles, strengthen and grow with training and weaken and atrophy with decreased physical activity. A child's physical fitness requires four components: overall fitness, mental fitness, joint fitness, and body composition fitness. The development of these components depends on the child's regularity in physical activity. The sports selection process faces the problem of subjectivity, particularly when using abstract observation, which, even if objective at the time, may not be so in the long run (the problem of prediction). Therefore, the coach must supplement their observations with anthropometric (body) measurements through morphological characteristics (height, weight, fat percentage, somatotype), physical measurements (endurance, speed, strength), physiological measurements (aerobic and anaerobic), measurements of technical skills, tactical thinking, and psychological and social skills, in addition to relying on high-level standards. In a study by Cazorla (1998), it was concluded that a high-level football player must possess the following specifications: - Height exceeding 180 cm ( (Predictable through genetic factors), - Body fat percentage not exceeding 11%, - 12 repetitions of a 20m sprint without losing 0.17 seconds compared to the best time, - Achieving a result equal to or greater than 65cm in the vertical jump (Abalakov) or 53cm in the counter-movement-jump (CMJ) test, - Achieving a maximum aerobic speed (VMA) equal to or greater than 17.5 km/h. Since selection is primarily aimed at children, who, as previously mentioned, experience rapid growth in all aspects of their physical, morphological, psychological, and mental development, influenced by numerous factors that must all be controlled—including the physical and sporting activities they engage in before specializing, whether through school sports programs in educational institutions or through their participation in semi-sports during childhood—what if these activities were controlled in a scientifically sound manner by subjecting the child to a multi-sports program with the goal of selecting them for football? This program aims to achieve integrated and harmonious development for the child, which will subsequently influence all aspects of athletic achievement.